Power and ground network topology optimization for cell based VLSIs - Mitsuhashi, T.; Kuh, E.S. ([1992] Proceedings 29th ACM/IEEE Design Automation Conference, 1992)
A new power and ground network design problem for cell-based VLSIs is discussed. In contrast to the conventional method, the network topology is optimized, or wiring resource consumption subject to electromigration and voltage drop constraints is minimized. The proposed method has been implemented. Using several examples, the validity of the problem formulation and the solution method was confirmed. Experimental results showed that brute power bus enhancement was meaningless and smart power and ground topologies significantly reduced the consumption of wiring resources.< >